The Influence of E-Service Quality and Service Features on Customer Trust in Gojek Application Users - Fazri Wima Maulana; Kartika Puspitasari Arrochimmi; Kiki Dianti; N Nurkomalasari; Adi Setiawan (Apollo: Journal of Tourism and Business, 2024)
This research was conducted to analyze the influence of E-Service Quality and Service Features on Customer Trust among Gojek application users. The data in this research was collected through distributing questionnaires and analyzed using quantitative analysis. The population taken was students at Swadaya Gunung Jati University with a sample of level 4 students. The sample taken was 208 respondents using a non-probability sampling technique, namely purposive sampling. In this study, the data was processed using SPSS version 25 with cross descriptive model analysis (Crosstab), as well as the relationship between the respondent's character and the question variables. And to test the data using validity and reliability tests. The research results show that E-Service Quality has a significant influence on Customer Trust, Service Features have a significant influence on Customer Trust, and the two variables between E-Service Quality and Service Features both have a significant influence on Customer Trust